MO464TWO-YEARS CHANGES IN ABPM, CARDIAC AND RENAL PARAMETERS PREDICT CARDIOVASCULAR OUTCOME OF PATIENTS WITH CKD AND HYPERTENSION. (29th May 2021) - Bussalino, Elisabetta; Ravera, Maura; Mallia, Laura; Minutolo, Roberto; Vettoretti, Simone; Paoletti, Ernesto
Abstract: Background and Aims: Changes over time in eGFR and albuminuria provide better accuracy than baseline values for end-stage risk prediction in CKD patients, whereas no studies have evaluated the impact of changes in renal, cardiac, and BP parameters on cardiovascular (CV) outcome. Methods: We prospectively evaluated 249 hypertensive CKD patients with available baseline and 2-year echocardiography and ambulatory blood pressure monitoring (ABPM). Outcome was a composite of death or any non fatal CV event. Predictors of outcome were tested by multivariable regression analysis. The accuracy of prediction models that included baseline and 2-year changes (Δ) in cardiac, renal and BP parameters was assessed by ROC analysis. Results: During a follow-up period of 71 months, 69 CKD patients (28%) experienced a major CV event or died. By multivariable Cox regression analysis baseline nighttime pulse pressure (PP) (HR 1.01, 95% CI 1.00 to 1.04), left ventricular mass (LVMi) (HR 1.03, 95% CI 1.02 to 1.04), ejection fraction (EF) (HR 0.96, 95% CI 0.90 to 0.97), Δ nighttime PP (HR 1.04, 95% CI 1.01 to 1.07), Δ LVMi (HR 1.02, 95% CI 1.00 to 1.04), and ΔEF (0.93, 95% CI 0.89-0.97) were associated with outcome. A model that includes 2-year changes in LVMi, EF, proteinuria, and nighttime PP was more accurate than a model that only evaluated baseline values (Δc-statistic 0.08, 95% CI 0.02 to 0.13, P=0.006; net reclassification improvement -NRI- 0.24, P= < 0.0001). Conclusion: Estimation of 2-year changes in renal, cardiac, and BP parameters improve the predictive accuracy of adverse CV outcome in CKD patients followed in tertiary care.